Analisis Penerapan Sistem Informasi Akuntansi Penggajian Dalam Menunjang Efektivitas Pengendalian Internal Penggajian - Intishar, Yayang; Muanas, Muanas (Institut Bisnis dan Informatika Kesatuan, 2018)
One that influences the success of the company is the system applied to the company, the payroll accounting information system. A payroll accounting information system is very influential for companies to support the effectiveness of internal control. The author conducted research at PT. Dwi Prima Rezeky, a company engaged in the manufacturing industry. The purpose of this study was to find out the description of salary payment transactions and to find out the application of payroll accounting information systems to support the effectiveness of internal control.This type of research is a type of descriptive research that uses primary data such as the results of interviews with companies and secondary such as organizational structure. Data collection techniques are carried out using observation, interview, and literature techniques. The data analysis method used is a descriptive method. The study was conducted at PT. Dwi Prima Rezeky is located on Jl. Raya Pemda Keradenan No. 12 Cibinong-Bogor.The results of this study indicate that PT. Dwi Prima Rezeky has implemented a payroll accounting information system already good enough because it has implemented the elements of an adequate accounting information system so as to support the effectiveness of internal control. However, in internal control, there are still a number of functions and systems of authorization that have not been implemented, namely the function of making salary lists and salary payments carried out by the financial function and the payroll is not checked again and not re-authorized by the accounting.